2008
DOI: 10.1109/tvcg.2008.166
|View full text |Cite
|
Sign up to set email alerts
|

Stacked Graphs – Geometry & Aesthetics

Abstract: In February 2008, the New York Times published an unusual chart of box office revenues for 7500 movies over 21 years. The chart was based on a similar visualization, developed by the first author, that displayed trends in music listening. This paper describes the design decisions and algorithms behind these graphics, and discusses the reaction on the Web. We suggest that this type of complex layered graph is effective for displaying large data sets to a mass audience. We provide a mathematical analysis of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
224
0
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(231 citation statements)
references
References 6 publications
1
224
0
6
Order By: Relevance
“…Havre et al [16] used the stacked graph to depict thematic variations over time within a large collection of documents. There is also work aiming at improving the aesthetics of the stacked graph [17,18]. In our work, we adapt a recommender engine to the stacked graph visualization.…”
Section: Related Workmentioning
confidence: 99%
“…Havre et al [16] used the stacked graph to depict thematic variations over time within a large collection of documents. There is also work aiming at improving the aesthetics of the stacked graph [17,18]. In our work, we adapt a recommender engine to the stacked graph visualization.…”
Section: Related Workmentioning
confidence: 99%
“…The priority of these rules may even be adjusted while a model is created. Prior research has shown that the comprehension of graphical layout of a model depends upon a number of parameters [10,28,30,31]. Some of these parameters have been identified as having a strong influence with respect to the understanding of a model [28,30].…”
Section: Graphical Layout and Understandingmentioning
confidence: 99%
“…However, as the scores are based only on a single attribute, the rankby-feature system does not address multi-attribute rankings and is thereforeonly tangentially relevant to our technique. The RankExplorer system by Shi et al [4] uses stacked graphs [3] with augmented color bars and glyphs to compare rankings over time. While the system effectively addresses the ranking comparison requirement (R X), it can only incorporate the information about the cause of the rank based on multiple attributes (R II and R III) by showing details on demand in a coordinated view fashion.…”
Section: Literature Reviewmentioning
confidence: 99%